A study of three Indonesian teachers' participation in a US graduate program - Nugrahenny T. Zacharias (Universitas Katolik Indonesia Atma Jaya, 2017)
Many research have focused on the identity construction of Asian teachers (see, among others, Chang, 2004; Cui, 2006; Ha & Que, 2006; Tang, 1997; and Tsui, 2007). Among all these, studies focusing on Indonesian teacher identity construction are rare. Thus, the study aimed at filling the gap. The study examined the identity development of three Indonesian English teachers navigating in an in-service program in the US. The study found that their identities varied with one subject experienced identity shift while others illustrate the case of identity as relatively permanent. Whereas previous studies on L2 teachers have focused primarily on the construction of teacher identity per se, the findings of the study indicated that the construction of the three Indonesian teacher identities were grounded in other identity options such as nonnative speaker, gender as well as learner identity.